The Concept of the Poet in Latif Halmet’s Poetic Text - Asaad Karem, Pshtiwan; Rashid Salih, Salim (Zanco Journal of Human Sciences, 2023)
The concept of the poet; Thanks to his invention—poetry—difference, function and source of invention; It has been viewed from many perspectives, from ancient times to the present; It has been identified as crazy, innovative, talented and experienced, depending on its different views and the role and position of his innovation. Latif Helmet; He is one of the most innovative poets of contemporary Kurdish literature and has played a significant role in the innovation of Kurdish poetic texts, he has spoken extensively about the characteristics of the poet and its duties in his poems, in which he has expressed his opinions and understandings about the poet directly and indirectly. In this study it is attempted to organize, present and analyze them. The research consists of: introduction, abstract and two sections: the first section is entitled: "The concept of the poet from different perspectives", theoretically about the concept of the poet in two themes are discussed and entitled by (Poet and Ordinary Human Being, Poet and Truth) in which the different aspects and different views of the poet from the perspective of philosophers and critics are presented. The second section is entitled: "The Concept of the Poet in Latif Halmet’s Poetic Text", Latif Halmet's views on the poet are presented in five topics entitled: (Poetry is not for the cowards, poetry or sadness, poetry between pride and personal interest, the position and role of the poet, poetry and madness). In conclusion, the results of the study are summarized in five points. Then the list of references used is presented, and the abstract is available in Arabic and English.